Digital literacy practices in tertiary education: A case of EFL postgraduate students - Aji Budi Rinekso; Rojab Siti Rodliyah; Intan Pertiwi (Universitas Syiah Kuala, 2021)
Over the past few decades, technologies grew rapidly, transforming traditional instructions to be more digitalized and stimulating many researchers to study digital literacy practices in a school-educational context. However, studies exploring digital literacy practices in the context of tertiary education are still scarce. Within the qualitative approach, this study investigated digital literacy practices by EFL (English as a Foreign Language) postgraduate students. Moreover, it intensively discusses the kinds of digital tools used by the participants and the purposes of using them. Additionally, the way the participants conceptualized digital literacy was also elaborated. Thirty-four EFL Master students of a public university in Bandung, Indonesia, participated in this study. An online open-ended questionnaire and semi-structured interviews were applied in data collection. Meanwhile, eight dimensions of digital literacy in the Hague and Payton’s frameworks were used as the basis of the thematical analysis of the interview data. Results showed that the participants conceptualized digital literacy as soft skills for managing digital information covering the acts of searching, comprehending, evaluating, creating, and sharing. The prominent result of this study relates to how the participants used digital tools for academic/research and general purposes. Subsequently, this study recommends that tertiary education institutions provide more training on maximizing digital tools for academic writing and broader access to prepaid journal articles. Further exploration of lecturers’ digital literacy practices is highly recommended.